Affordances of social technologies as social microworlds - Zaphiris, Panayiotis; Parmaxi, Antigoni (My University, 2014)
Social technologies such as blogs and wikis have been used extensively in multiple educational settings for diverse purposes. Despite their popularity, their potentiality is not fully exploited, whereas their use is not clearly framed in theory. In this poster we present the potential of social technologies as social microworlds for facilitating groups of learners to construct a shareable artifact. A qualitative study that captures the use of different types of social technologies in three different classroom settings sheds light on the affordances of social technologies to transform the activity of learning across a new culture of computational tools.
Keywords: Social technologies; Blogs; Wikis; Multiple educational settings